Extension of the Innovation Life Cycle Based on the Industry Market Regulator of Innovative Market Products - LOGINOVA, Olga Aleksandrovna; EFREMOV, Andrey Aleksandrovich; SEKERIN, Vladimir Dmitriyevich; GOROKHOVA, Anna Evgenievna; BANK, Sergey Valeryevich (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The article proposes to consider the innovation life cycle by the innovation marketing method from the perspective of a systematic approach as part of a complex system of the innovation process. The authors have offered a digital service named ‘Market regulator of innovative products’ which has industry market monitoring and commercial intermediary functions, unifying innovators and investors on the same platform with the assistance of market experts in the areas such as marketing, information technology, scientific analysis, and investment. In case of sales decline, industry-specific customer, a commercial customer, or a small business market product can receive a service aimed at extending the innovation life cycle of its high-tech product. This additional stage of the life cycle of an innovative high-tech product the authors call the innovations diffusion stage where a high degree of uncertainty is compensated by the market mechanism of the competition of ideas and investments.